Optimizing Injection Molding Parameters to Cycle Time of Bioring Cone Cup Products with Taguchi Method - Farizi Rachman; Bayu Wiro Karuniawan; Ika Pramestiani; Noorman Rinanto (International Journal of Marine Engineering Innovation and Research, 2023)
At the Sukodono molding company which produces Bioring cone cups using injection molding machines, a trial and error process to obtain parameter setting values on the machine is still applied in the early stages of production. This problem is detrimental to the company because they have to bear the production burden due to production delays. A solution is needed to optimize injection parameters with cycle time response. Therefore, this study proposes an analysis of the application of the Taguchi method by utilizing the signal for noise ratio to determine the influence of factors and also to optimize parameter such as temperature, pressure, and cooling time for the production process. The trial results show that the ideal blend of factors includes injection pressure parameters at level 1 with a value of 80 bar, injection temperature at level 2 in value of 225°C, and cooling time in level one with a value of 0.1 seconds.